1969
DOI: 10.1680/geot.1969.19.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Discontinuous Rocks in Direct Shear

Abstract: SYNOPSISThe strength of discontinuous rocks under direct shear loading is examined analytically and experimentally.In the direct shear test a homogeneous and isotropic block of rock may fail by three mechanisms: failure in tension, failure in shear and failure at ultimate strength. The strength parameters include the tensile strength, fundamental shear strength (cohesion), angle of internal friction, the angle of friction at ultimate strength and the normal stress on plane of enforced shear.The direct shear st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
3

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(68 citation statements)
references
References 1 publication
2
63
0
3
Order By: Relevance
“…Laijtai performed the direct shear test on the intermittent jointed rock mass, and the composite damage theory was put forward [13]. Based on the equivalent rock mass (ERM) technique, Zhou et al performed the triaxial compression simulation on the jointed rock mass using the PFC 3D software [14].…”
Section: Introductionmentioning
confidence: 99%
“…Laijtai performed the direct shear test on the intermittent jointed rock mass, and the composite damage theory was put forward [13]. Based on the equivalent rock mass (ERM) technique, Zhou et al performed the triaxial compression simulation on the jointed rock mass using the PFC 3D software [14].…”
Section: Introductionmentioning
confidence: 99%
“…[6,7]). Lajtai [8] performed direct shear test on natural rock specimens with two parallel slots, tensile wing cracks were found to first appear at the tips of horizontal joints, followed by the secondary shear cracks propagating towards the opposite joint.…”
Section: Figmentioning
confidence: 99%
“…[6,7]). Lajtai [8] performed direct shear test on natural rock specimens with two parallel slots, tensile wing cracks were found to first appear at the tips of horizontal joints, followed by the secondary shear cracks propagating towards the opposite joint. Also he observed that the failure mode changed with increasing normal stress; he suggested a composite failure envelope to describe the transition from the tensile strength of the intact material to the residual strength of the discontinuities.…”
Section: Figmentioning
confidence: 99%
“…Intermediate principal stress slightly affected the strength of rock mass when such stress occurred parallel to the joint. Laijtai [4] performed the direct shear test to intermittent jointed rock mass, proposed composite damage theory, and found that body strength was a product of the rock block and joint contribution. Niu et al [6] used the numerical method to examine the sensitivity of jointed rock mass to various factors.…”
Section: State Of the Artmentioning
confidence: 99%